Učinkovitost programa "Spodbujajmo nekajenje" pri prvi generaciji slovenskih osnovnošolcev - Koprivnikar, Helena (Zdravstveno varstvo, 2009)
Aim: The aim of the study was to estimate effectiveness of the primary school-based programme ''Let''s Promote Nonsmoking'' with describing its effects on knowledge and attitudes about tobacco and also smoking behaviour ofyouth. Methods: We compared knowledge and attitudes about tobacco and health consequences of tobacco use and also different measures of smoking behaviour between primary school pupils, who were participating in nonsmoking promotion programme of six years duration and primary school pupils, who were not participating in the programme. In our study we used a questionnaire and surveyed 1.055 pupils aged 14 to 16 from 20 primary schools from different parts of Slovenia, 560 were from primary schools in which the programme was implemented and 495 from primary schools without the programme. The study was carried out during the period from May to June 2006. Results: We demonstrated positive effects of the programme on knowledge, attitudes and smoking behaviour of primary school pupils. The programe sigificantly increased the overall knowledge in youth of both genders, significantly increased attitudes against tobacco in girls and share of never smokers in boys. We have not demonstrated significant changes in other measures of youth smoking behaviour. Conclusions: School-based smoking prevention programmes are one of the effective measures for decreasing tobacco use among youth. Programme ''Let''s Promote Nonsmoking'' also demonstrates positive effects on knowledge, attitudes and smoking behaviour of primary school pupils. Results of our study and data from foreign scientific literature support continued implementation and also renovation and updating of the programme ''Let''s Promote Nonsmoking''.
Keywords: child; kajenje; mladostniki; otroci; programi